Estudo de correlações entre propriedades do concreto e ensaios não destrutivos - Araújo, Carla Cavalcante (2018)
The non-destructive tests are an important tool in the evaluation of concrete properties both during and after finishing the execution of structures. In this type of evaluation, correlation curves can be used to the indirect determination of these properties. However, these correlations should be specific to the materials and application conditions under analysis. This study sought to obtain correlation curves between properties of concrete used in the region of João Pessoa-PB and non-destructive tests. For this purpose, sclerometry and surface electrical resistivity measures associated with compressive and tensile strength results were used in concrets of three resistance classes and at five different ages. The results of this research provide correlation curves with significant adjustments between the analyzed variables, which reliably characterize the properties of the different tested concretes. The curves can be used to evaluate the produced concretes in the region of João Pessoa-PB, with a similar composition (cement CP V ARI) and with compressive strength values within the range of 30 MPa to 50 MPa at 28 days.